PHYTOCHEMICAL PROFILE AND IN VITRO BIOACTIVITIES OF AGELANTHUSDODONEIFOLIUS: ANTIMALARIAL, ANTIMICROBIAL, AND ANTIOXIDANT EFFECTS (Wudil Journal of Science and Technology Education, 2025)
Agelanthusdodoneifolius (Loranthaceae), a hemi-parasitic plant widely utilized inNorthern Nigerian ethnomedicine for treating malaria, wounds, and infections, wasevaluated for its phytochemical composition and in vitro bioactivities to validate itstraditional use. Aqueous, chloroform, and ethanol leaf extracts were subjected toqualitative phytochemical screening, revealing tannins, glycosides, saponins, phenols,and flavonoids, but lacking alkaloids, anthraquinones, and phlobatannins. In vitroantimalarial activity against Plasmodium falciparum (5% parasitemia) was determinedusing the Giemsa staining method. The chloroform and ethanol extracts exhibited dose-dependent activity, with the chloroform extract achieving 84.7% parasite elimination at10 mg/mL after 48 hours—significantly higher than the ethanol extract (82.4%, p =0.0145), though less potent than artemether (92.7%). Antimicrobial activity, assessed viathe broth microdilution method against Staphylococcus aureus (ATCC 25923),Escherichia coli (ATCC 25922), and Candida albicans (ATCC 10231), revealedminimum inhibitory concentrations of 0.625–5 mg/mL for ethanol extracts and 1.25–10mg/mL for chloroform extracts, supporting its traditional application in wound healing.Antioxidant activity determined by the DPPH assay showed IC₅₀ values of 0.45 ± 0.03mg/mL (ethanol) and 0.82 ± 0.05 mg/mL (chloroform), indicating strong radicalscavenging potential compared to ascorbic acid (0.02 ± 0.01 mg/mL). These findingsvalidate the ethnomedicinal relevance of A. dodoneifolius and underscore its potential asa source of antimalarial, antimicrobial, and antioxidant agents. Further work shouldisolate its bioactive constituents, elucidate mechanisms of action, and evaluate in vivoefficacy for therapeutic development.
Keywords: Agelanthusdodoneifolius, hemi-parasitic plant, phytochemical composition, in vitro bioactivities, malaria, wounds, infections, phytochemicals.